COMPUTATIONAL STRUCTURAL INTEGRITY ANALYSES OF A CANARD BOX-WING UNMANNED AERIAL VEHICLE (UAV) PLATFORM FOR DISASTER MANAGEMENT AND AGRICULTURAL SURVEILLANCE APPLICATIONS - Patadlas, Aiza A; Remocaldo, Genesis N; Ambos, Edgar C; Maglasang, Jonathan C (Journal of Agriculture and Technology Management, 2020)
The modern concern on energy, efficiency and environment leads to the development of unconventional designs of an unmanned aerial vehicle (UAV) platform of box-wing configuration for agricultural surveillance, risk and disaster management and other civilian applications. The box-wing configuration used in this study was based on Prandtl’s best wing system which gives the smallest possible induced drag for a given wing span and height. In this study, the structural integrity of the designed UAV was evaluated using finite element method software. The aerodynamic loads resulting from the computational fluid dynamics (CFD) simulations were exported to the finite element method solver in SolidWorks™ for stress analyses. The maximum stresses with and without gust are and, respectively, which are still below the rapture strength of Balsa wood which is at  . The designed UAV was equipped with a spring- damper system in order to avoid severe damage due to impact forces during landing. The front and aft wings have flutter speeds of  and, respectively. The designed Prandtl box-wing was able to reach. When a wind gust of  was introduced in a cyclic fashion the load factor  reaches  but still without detrimental effects being observed in the structure. The overall computational fluid dynamics and structural analyses results showed that the designed box-wing UAV for efficient disaster management and surveillance applications could perform well and withstand the projected loading conditions during various flight missions.